(untitled) (Mustansiria Dental Journal, 2019)
systematic approach to removable partial denture design is difficult and requires thought planning. The correct design must be based upon accepted mechanical and biological principles. This is an experimental study for drawing partial denture design for selected cases on papers by different levels of participants and compares these designs with a standard design taken mainly from a text book "McCracken’s Removable partial prosthodontics". The results of this study shown that the highest percentage of acceptable design for the total of three selected components ( major connector, rest and retainers) was 67.91% made by Prosthodontists followed by 49.16 made by students, 29.58% made by general dental practitioners and finally the lowest percentage was 23.33 that made by dental technicians .Also there are great variations seen in different designs, some of them were far away from the principles of removable partial denture design, that lead to put in mind for more focusing on studying removable partial denture design in dental schools.